Exploration of Clay In Luhak Limo Puluah As A Source Of Raw Materials For Pottery Art - Prastawa, Wisnu; Sriyanto, Sriyanto; Kasman, Selvi; Akmal, Ahmad (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2025)
The high potential of natural resources in West Sumatra, Indonesia, especially clay, provides benefits for the community to increase income economically and artistically imaginatively as an industrial product and can be converted into raw materials for pottery art. The purpose of this study is to base the potential of clay as a raw material for pottery crafts by identifying, studying, and producing clay as a raw material for pottery crafts in Lima Puluh Kota Regency, West Sumatra. This study uses a mixed method through a creative approach as a basis for the study and creation of ceramic craft art supported by laboratory testing. 50 Kota clay provides new imaginative raw materials for pottery art, where the Harau District area has the potential for developing clay as pottery art with a clay content of 51.74% with a color of 10 YR 7/8 (orange-yellow). This test can be used as a basis for developing new ideas from the results of converting red brick products into high-value pottery art products in various forms (figurative and abstract), visual and functional through art production technology (such as twisting, printing, and turning).